Grapevine Shoot Extract Rich in Trans-Resveratrol and Trans-ε-Viniferin: Evaluation of Their Potential Use for Cardiac Health - Contreras, María del Mar; Feriani, Anouar; Gómez-Cruz, Irene; Hfaiedh, Najla; Harrath, Abdel Halim; Romero, Inmaculada; Castro, Eulogio; Tlili, Nizar (Foods, 2023)
A grapevine shoot extract (GSE) was obtained using ultrasound-assisted extraction and characterized. The main phenolic constituents were identified as stilbenoids. Among them, trans-resveratrol and trans-ε-viniferin stood out. The GSE was administered to an isoproterenol-induced myocardial injury animal model. The extract alleviated the associated symptoms of the administration of the drug, i.e., the plasma lipid profile was improved, while the disturbed plasma ion concentration, the cardiac dysfunction markers, the DNA laddering, and the necrosis of myocardial tissue were diminished. This effect could be related to the anti-oxidative potential of GSE associated with its antioxidant properties, the increased levels of endogenous antioxidants (glutathione and enzymatic antioxidants), and the diminished lipid peroxidative markers in the heart. The results also revealed angiotensin-converting enzyme (ACE)-inhibitory activity, which indicated the potential of GSE to deal with cardiovascular disease events. This work suggests that not only trans-resveratrol has a protective role in heart function but also GSE containing this biomolecule and derivatives. Therefore, GSE has the potential to be utilized in the creation of innovative functional ingredients.